Hypothesized mechanisms of death in swimming: a systematic review - Yao, Y.; DiNenna, M. A.; Chen, L.; Jin, S.; He, S.; He, J. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background The study aims to update the specific classification of mechanisms of death in swimming and to demonstrate these categories are reasonable, by analyzing more characteristics of death cases, evaluating the available evidence and determining their quality.